The impact of lifestyle factors on the clinical outcomes of in vitro fertilisation-embryo transfer (IVF) treatment - Joesbury, Karen Ann (Curtin University, 2003)
Objectives: To determine the effect of female and male cigarette smoking, caffeine and alcohol consumption, stress and indicators of dietary status on the clinical outcomes of NF treatment. Design: Prospective cohort study. Setting: PIVET Medical Centre, Perth, Western Australia. Patients: Of 351 couples who commenced IVF treatment at PIVET Medical Centre between January 1997 and August 1998, 281 females and 247 males participated in this study, generating participation rates of 80.1% and 70.4%, respectively. Main Outcome Measures: Multivariate methods of data analyses were used to control for patient and treatment variables in the examination of the effect of lifestyle factors on the following clinical outcomes: 1) number of oocytes retrieved by transvaginal oocyte aspiration (oocyte production), 2) fertilisation, measured as the number of oocytes fertilised weighted by the number of oocytes inseminated, 3) B-hCG pregnancy, 16 days post-embryo transfer, and 4) <12 week pregnancy loss following confirmation of B-hCG pregnancy. As a measure of ovarian reserve, serum basal FSH levels were also investigated as a dependent variable. Lifestyle factors included years of cigarette smoking (smoke years), tobacco, alcohol, caffeine and fruit and vegetable consumption, and stress from daily living and NF treatment. Results: Daily stress, tobacco consumption and smoke years were the female lifestyle factors shown to have a significant effect on NF treatment. Oocyte production decreased with increasing levels of daily stress (P=0.039). However, female patients with high daily stress levels experienced higher than average rates of fertilisation in vitro (P=0.0059) and pregnancy (P--0.0207). Smoke years had an adverse effect on ovarian reserve (P=0.035), which in turn, compromised oocyte production.Female smoke years was negatively associated with rates of fertilisation (P<0.0001), and this effect was exacerbated by cigarette smoking at the time of treatment (P=0.0187). Of the male lifestyle factors, caffeine, alcohol and fruit and vegetable consumption and IVF stress affected fertilisation in vitro. Fertilisation increased with alcohol consumption (P<0.0001), and with fruit and vegetable consumption (P<0.0001). A significant interaction term between these two factors (P=0.0144) implied a threshold of benefit from the combined effect of the consumption of alcohol and fruit and vegetables. Caffeine consumption negated the beneficial effect of alcohol consumption, as shown by a significant interaction term between alcohol consumption and caffeine consumption (P=0.0007). Male stress from NF treatment had an adverse effect on rates of fertilisation in vitro (P<0.0001). Cigarette smoking by the male partner increased the likelihood of the female partner experiencing a <12 week pregnancy loss (P=0.0084). Conclusions: In meeting with its principal objective, this study has demonstrated that specific lifestyle factors impact on the clinical outcomes of IVF treatment. It confirms the findings from former studies, namely the adverse effect of female smoking on ovarian reserve, and daily stress on ovulation. Moreover, this study has identified numerous new and unexpected relationships. Of note, the positive effect of male alcohol consumption on fertilisation in vitro and the elevated risk of early pregnancy loss associated with male smoking. This study has paved the way for future research into the identification of specific mechanisms of effect, including those suggested.